Penulisan Buku Perjalanan Al-Qur’an Tua di Bumi Persaudaraan, Dakwah Kesultanan Ternate di Alor - Rahmad Nasir; Abdullah R S (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
There are not many scientific texts comprehensively containing the history of the entry of Islam in Alor district, especially from the Sultanate of Ternate, besides that there are not many Islamic Religion teachers in Madrasas who teach students about this. Even the lessons of Islamic Cultural History (SKI) that are taught are also very general in nature which are taught throughout Indonesia and even in the world. Meanwhile, the discussion of Special SKI conditions in Alor Regency seems to be rare. It is also difficult to find preachers / missionaries conveying in religious pulpits. Among the thirst of the Alor community, especially Alor Muslims for the identity of Islam in Alor, the service team tried to carry out service activities for writing the book